Rapid Reduction of Alkenes and Alkynes over Pd Nanoparticles Supported on Sulfonated Porous Carbon - Arash Shokrolahi; Abbas Zali; Kamal Ghani (Journal of Chemistry)
A novel method has been introduced for rapid reduction of alkenes and alkynes, which may be attractive for chemical industries. This method has some advantages such as simplicity and low cost of reactants. Pd supported on sulfonated porous carbon (SPC) was used as a new catalyst for reduction of alkenes and alkynes to the corresponding alkanes using sodium borohydride. The heterogeneous reaction was conducted in open air at room temperature to produce the desired saturated compounds in high yields (over 96%) and in short reaction time (15 minutes).